GROUNDWATER FLOW MODELING IN CONSERVATION AREA IN SOUTHWEST PART OF SÃO PAULO STATE, BRAZIL - Pinheiro, M. P. M. A.; Manzione, R. L. (Revista Brasileira de Engenharia de Biossistemas, 2019)
This work was developed to provide a specific knowledge about the hydrogeological behavior of the Avaré Ecological Station (EEcAv) area, especially the groundwater flow dynamics, showing the importance of preserving the environmental conservation areas of the State of São Paulo for water security. The study area located in the municipality of Avaré/SP-Brazil occupies a territorial extension of approximately 720 hectares. For this study a 30-meter Shuttle Radar Topography Mission (SRTM) digital elevation model was used; and the following software to support the analysis: QGIS, SAGA and MapWindow (extension TauDEM). With the help of these tools it was possible to model groundwater flow by estimating the Flow Direction, Accumulated Flow and Topographic Moisture Index (ITU) of the area. With the obtained results it was verified that the underground flow of the EEcAv is directed to the places with higher humidity, that is, the Novo and Pardo rivers. It also shows that the station is situated between water corridors reinforcing its environmental importance.